Tourism Awareness Movement through Educreative Program in Dunggala Village, Bone Bolango District - Danial, Hari; Mestari, Sri Agriyanti; Sambouw, Elsje Louise (Bima Abdi: Jurnal Pengabdian Masyarakat, 2022)
Dunggala Village is one of the villages in Tapa District, Bone Bolango Regency which is the center of Miranti bathing tourism and the tomb of King Blongkod. Not to mention, currently the Dunggala Village area is a rafting destination located at Langge Hils Resort. But unfortunately, the lack of public attention, including tourists, government and business actors towards tourism awareness, makes this not work well, including there are still many street vendors who do not pay attention to the cleanliness of their merchandise and place, lack of good interaction in entertaining guests using English. as well as Indonesian. Many of the community components do not pay attention to the importance of tourism awareness as an intervention in community economic development. The MBKM program "Building a Village" aims to empower the community through a tourism awareness movement based on educative programs for the community. This program is implemented through methods of education and training, mentoring, service and coaching which are expected to be sustainable through the awareness of related parties, especially the government and village parties in paying attention to tourist destinations that have the potential to improve the community’s economy. In addition, to support the tourism awareness movement, it is hoped that it can form a tourism awareness group, create a tourism center for the local community.